Profile and entrepreneurial intention of nursing students: a comparison between Brazil and Chile - Rosana Maria Barreto Colichi; Verónica Gómez-Urrutia; Andres Eduardo Jimenez-Figueroa; Hélio Rubens de Carvalho Nunes; Silvana Andrea Molina Lima (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to identify and compare factors associated with profile, intentions, motivations, and barriers to entrepreneurial behavior of nursing students from Brazil and Chile. Methods: this cross-sectional study was carried out between March and September 2018 including 889 nursing students. A form was used to assess the socio-demographic profile, professional claims, entrepreneurial intentions and motivations. Statistical analysis used Chi-Square and Fisher's Exact tests, with a 5% significance level, and a simple logistic regression model. Results: there are significant differences between countries in the profile of students and in the motivations studied, but not in professional pretensions and entrepreneurial intentions. Lack of education on the subject reveals itself as an important barrier to entrepreneurship. Conclusion: given the lack of teaching entrepreneurship in undergraduate nursing courses and the characteristics inherent to students, education must be appropriate to different cultures to prepare future professionals for other areas of practice.